Answer:
8
Step-by-step explanation:
1. 3b - 2 (1 - b) / a - 2
2. 3(2) - 2 (1 - 2) / 3 - 2
3. 6 - 2 (-1) / 1
4. 6 + 2 / 1
5. 8 / 1
6. 8
4y + 228 = 352
4y = 352 - 228
4y = 124
--- ----
4 4
------------
| y = 31 |
------------
hope this helps
Step-by-step explanation:
I will solve your system by substitution.
(You can also solve this system by elimination.)
4x+y=17;4x−3y=−3
Step: Solve4x+y=17for y:
4x+y+−4x=17+−4x(Add -4x to both sides)
y=−4x+17
Step: Substitute−4x+17foryin4x−3y=−3:
4x−3y=−3
4x−3(−4x+17)=−3
16x−51=−3(Simplify both sides of the equation)
16x−51+51=−3+51(Add 51 to both sides)
16x=48
16/x = 48/16
(Divide both sides by 16)
x=3
Step: Substitute 3 for x in y=−4x+17:
y=−4x+17
y=(−4)(3)+17
y=5(Simplify both sides of the equation)
Answer:
x=3 and y=5
Problem
evaluate the function
f(-x) = f(x)
plug in the points (2,1) then solve
Solution
For this case we can conclude that:
f(2) =1
So then we satisfy that:
f(-2) =1
The more observations you make the closer and closer the experimental probability will approach the theoretical probability. In this case the theoretical probability is:
P(HH)=(1/2)(1/2)=1/4
So in 105 trials one would expect to get two heads:
105(1/4)=26.25 times.